Magnetic resonance imaging detects onset and association with lung disease severity of bronchial artery dilatation in cystic fibrosis - Leutz-Schmidt, Patricia; Optažaite, Daiva-Elžbieta; Sommerburg, Olaf; Eichinger, Monika; Wege, Sabine; Steinke, Eva; Gräber, Simon Y.; Puderbach, Michael; Schenk, Jens-Peter; Alrajab, Abdulsattar; Triphan, Simon M. F.; Kauczor, Hans-Ulrich; et al. (ERJ Open Research, 2023)
Background Bronchial artery dilatation (BAD) is associated with haemoptysis in advanced cystic fibrosis (CF) lung disease. Our aim was to evaluate BAD onset and its association with disease severity by magnetic resonance imaging (MRI). - Methods 188 CF patients (mean±sd age 13.8±10.6 years, range 1.1-55.2 years) underwent annual chest MRI (median three exams, range one to six exams), contributing a total of 485 MRI exams including perfusion MRI. Presence of BAD was evaluated by two radiologists in consensus. Disease severity was assessed using the validated MRI scoring system and spirometry (forced expiratory volume in 1 s (FEV1) % pred). - Results MRI demonstrated BAD in 71 (37.8%) CF patients consistently from the first available exam and a further 10 (5.3%) patients first developed BAD during surveillance. Mean MRI global score in patients with BAD was 24.5±8.3 compared with 11.8±7.0 in patients without BAD (p<0.001) and FEV1 % pred was lower in patients with BAD compared with patients without BAD (60.8% versus 82.0%; p<0.001). BAD was more prevalent in patients with chronic Pseudomonas aeruginosa infection versus in patients without infection (63.6% versus 28.0%; p<0.001). In the 10 patients who newly developed BAD, the MRI global score increased from 15.1±7.8 before to 22.0±5.4 at first detection of BAD (p<0.05). Youden indices for the presence of BAD were 0.57 for age (cut-off 11.2 years), 0.65 for FEV1 % pred (cut-off 74.2%) and 0.62 for MRI global score (cut-off 15.5) (p<0.001). - Conclusions MRI detects BAD in patients with CF without radiation exposure. Onset of BAD is associated with increased MRI scores, worse lung function and chronic P. aeruginosa infection, and may serve as a marker of disease severity. - Tweetable abstract ERSpublications - click to tweetBronchial artery dilatation in patients with cystic fibrosis can be detected with chest magnetic resonance imaging (MRI) and may occur as early as preschool age. It is strongly associated with lung disease severity on MRI and spirometry. https://bit.ly/3PvUDqL
Gesehen am 22.05.2023